Increased tissue concentrations of histamine in the duodenal mucosa of children with coeliac disease. Issue 6 (June 1982) - Challacombe, D N; Dawkins, P D
Abstract : Tissue concentrations of histamine have been estimated in peroral duodenal biopsy specimens from five children with coeliac disease while on a gluten-free diet and after a three-month gluten challenge. Histamine concentrations in the patients on a diet did not differ significantly from a group of control children. However after gluten challenge, histological relapse of the duodenal mucosa in each patient was associated with increased tissue concentrations of histamine. The findings suggest that histamine may be involved in the pathogenesis of the small intestinal mucosal changes in children with coeliac disease.